Middle East Historiography: Did We Miss the Cultural Turn? - Martin, Kevin W. (History compass, 2014)
In the late 20th century, a novel mode of historical research and writing emerged and soon acquired its distinctive label, "the new cultural history." By the first decade of the current century, some deemed cultural history to have achieved hegemonic status within the historical profession. Yet recently mounted retrospective assessments of this "cultural turn" have cast doubt on such triumphalist declarations. This is especially so within the field of Middle East historiography, in which cultural history per se has failed to achieve the status of an identifiable sub-discipline on a par with social, economic, or political history. This essay explores possible explanations for this conspicuous absence, focusing on the distinctive history of the Western historiography of the Middle East and the tendency of disciplinary mainstreams to "domesticate" their unruly "children."